The Effectiveness of the Implementation of the Indonesian Standard Quick Response Payment System (QRIS) on MSMEs in Banten - Annissa Pratiwi (Review of Accounting and Taxation, 2022)
Purpose - This study aims to provide an overview of the effectiveness of implementing the Indonesian Standard Quick Response Payment System as an alternative digital payment method that can be used by small and medium businesses Design/methodology/approach - qualitative descriptive method is used as a research method that is applied in this study. the data in the study were taken from small and medium business owners in the province of Banten. data collection through structured interview techniques and literature study Finding - the implementation of the Quick Response Payment System has had a positive impact in supporting the business development of small and medium enterprises. the presence of this digital payment method encourages the acceleration of the payment transaction process, easier recording of business results and up-to-date business processes so as to attract more customer spending power with the various conveniences presented. Originality -